Comparison of computed tomography angiography versus cardiac catheterization for preoperative evaluation of major aortopulmonary collateral arteries in pulmonary atresia with ventricular septal defect - Rajesh Krishnamurthy; Farahnaz Golriz; Benjamin J Toole; Athar M Qureshi; Matthew A Crystal (Wolters Kluwer Medknow Publications, 2020)
Introduction: Pulmonary atresia with the ventricular septal defect is a rare congenital heart defect with high anatomic variability. The most important management question relates to the sources of pulmonary blood flow. The ability to differentiate between ductal dependence and major aortopulmonary collateral arteries is critical to achieving good outcomes and avoiding life-threatening hypoxia in the postneonatal period. Having accurate information about pulmonary arteries, major aortopulmonary collateral arteries, and sources of blood supply to each pulmonary segment is crucial for choosing the optimal surgical strategy. The purpose of this study is to compare computed tomography angiography (CTA) with cardiac catheterization for anatomic delineation of surgically relevant anatomy in pulmonary atresia with ventricular septal defect with major aortopulmonary collateral arteries. Materials and Methods: Retrospective review of all children with pulmonary atresia with ventricular septal defect with major aortopulmonary collateral arteries cared for at a large tertiary children's hospital who underwent cardiac catheterization with angiography and CTA close to each other without interval therapy. All studies were performed between 2007 and 2011. Results: There were 9 patients who met the inclusion criteria. Pulmonary artery anatomy (confluent vs. nonconfluent) was correctly identified in 9 patients by CTA and 8 patients by catheterization. There were no significant differences between CTA and catheterization in the identification of major aortopulmonary collateral arteries (mean = 3.4 collaterals/study via catheterization; mean = 3.1 collaterals/study via CTA; P = 0.67). CTA was superior to catheterization in the delineation of segmental pulmonary blood flow (P = 0.006). Conclusion: CTA and catheterization are equivalent in their ability to delineate pulmonary artery anatomy and major aortopulmonary collateral arteries.